Il linguaggio del trolling. Ingredienti semiotici, cause socioculturali ed effetti pragmatici - Leone, Massimo (Rivista Italiana di Filosofia del Linguaggio, 2020)
The article singles out and describes the main rhetorical ingredients of trolling through contrasting it with comparable discursive practices: provocation, joke, defensive anonymity, critical public discourse, controversy, and lie. The following elements are found to play a major role in the discursive construction of trolling: topic-insensitive provocation; time-boundless jest; sadistic hierarchy of sender and receiver; anonymity of both the troll and her or his audience; choral character of the ‘actant observer’ of trolling; construction of artificial contradictory semantics; disruption of argumentative logics; irrelevance of the relation between beliefs and expressions. Trolling profoundly disrupts the conversational ethics of the human civilization because it severs expression from content, signifier from signified, communication from intention.